Workshop on Review of Rejected Refugee Claims - Refugee Law Research Unit, Centre for Refugee Studies (Refuge: Canada’s Journal on Refugees, 1993)
On September 18 ,1992 the Refugee Law Research Unit of the Centre for Refugee Studies (CRS), Amnesty International and Vigil sponsored a workshop to review the process for the Review of Rejected Refugee Claims. The following is an account of the discussion at this workshop and reflects the efforts of concerned parties to understand the history and current state of affairs in the review of rejected refugee claims.